SEX DIFFERENCES OF VLF100 AND VLF50 SPECTRUM OF HEART RATE VARIABILITY IN HEALTHY INDIVIDUALS OF YOUNG AGE AND OLDER SUBJECTS WITH VASCULAR PATHOLOGY IN TERMS OF SEVEN-TEST, HYPERVENTILATION AND ORTHOSTASIS - Флейшман, Арнольд Наумович; Кораблина, Татьяна Валентиновна; Халиулин, Игорь Германович; Петровский, Станислав Альфредович; Неретин, Артем Андреевич (Medicine in Kuzbass, 2017)
Subject. About minute rhythms of heart rate variability (HRV) (VLF100 and VLF50) and their role in sex differences of HRV and autonomic provision of the body.Objective – to give a comparative evaluation of sex differences of the autonomic provision of the body in young adults of different constitutional and autonomic types and in the subjects of older age in vascular pathology in terms of functional loads based on the analysis of new indices of the oscillations with a period of 100 seconds (VLF100) and the oscillations with a period of 50 seconds (VLF50) in the spectrum of heart rate variability.Methods. Physiological methods included a five-step registration of heart rate with functional tests of low intensity (seven-test, deep breathing and active orthostasis). Mathematical methods are the following: spectral analysis of HRV based on continuous wavelet transform and Hilbert-Huang transform, correlation analysis.Main results. Sex differences were detected best in young people as under autonomic balance, as with the predominance of sympathetic or parasympathetic processes in terms of VLF100 and VLF50 in the combination with the oscillations of 10 seconds (LF) and the oscillations of high frequency (HF) and correlation analysis. Sex differences were significantly reduced in older individuals with tachycardia with a marked decrease of energy of wave processes. Unlike women functional loads increased the power of 10 sec. rhythms in men with vagal dominance. In the adaptive processes during orthostatic load sex differences were determined in individuals with initial optimal autonomic support.Conclusion. The results of sex differences of the new VLF100 and VLF50 indicators and their interconnection with LF and HF were essential to the study of autonomic provision in the body, characterizing central mechanisms of regulation.
Keywords: sex differences; Very Low Frequency 50 and 100 (VLF50; VLF100); heart rate variability; spectral Fourier and wavelet analysis; sympatho-vagal regulation; orthostatic tachycardia; correlation analysis